Practice Patterns and Learning Curve in Transoral Endoscopic Thyroidectomy Vestibular Approach With Neuromonitoring - Kuo, Ting-Chun; Duh, Quan-Yang; Wang, Yi-Chia; Lai, Chieh-Wen; Chen, Kuen-Yuan; Lin, Ming-Tsan; Wu, Ming-Hsun (Frontiers in Endocrinology, 2021)
Objectives Intraoperative neuromonitoring has not been routinely applied in early experience with the transoral endoscopic thyroidectomy vestibular approach (TOETVA). Because the preparation and surgical interventions are much different from conventional thyroidectomies, most endocrine surgeons willing to adapt to TOETVA lack access to information regarding the practice pattern and proficiency in the learning curve. We aimed to investigate the outcomes and to define the learning curve for TOETVA in this study. Methods A retrospectively analysis TOETVA patients between December 2016 through July 2019 treated at our hospital. The Cumulative sum graphic model was used to implement the learning curve as a surrogate for procedural proficiency. Results The 119 patients had mean age of 44.65 years and mean body mass index of 22.49 k/m2; included 107 women, 20 thyroiditis, and 106 hemithyroidectomy. The learning curve revealed two phases, an initial (35 cases) and a mature (84 cases) phase, for surgeons based on operation time (144.2 vs. 114.2 minutes, p= 0.0001). There were more bilateral thyroidectomies (15.5% vs. 0, p= 0.0100), larger indicated nodules (6.06 cm3 vs. 3.32 cm3, p= 0.0468), or larger thyroid to resect (16.38 cm3 vs. 8.75 cm3, p= 0.0001) in the mature phase. Procedure-related complications decreased significantly in the mature phase in comparison to the initial phase (3.57% vs. 31.43%, p= 0.0001). Conclusions The learning curve of TOETVA with neuromonitoring is 35 cases. With the accumulation of proficiency, the indications will expand. Step-by-step improvements from the experience of each case can reduce procedure-related complications.